Economic viability: a study on natural products store in the municipality of Cacoal and Pimenta Bueno/RO (Research, Society and Development, 2022)
This article aims to study the economic and financial viability of setting up a natural products store in the municipality of Cacoal and Pimenta Bueno/RO. Techniques of Net Present Value (NPV), Internal Rate of Return (IRR) and Payback (Period of Return on Investment) were used. Weighted averages were performed on the results indicated by the research participants, for the survey of economic viability. The specific objectives of this article were to identify initial investment values, describe product lines and price margins, in addition to projecting direct and indirect costs and calculating the viability of the business. The calculations were based on the cash flow projected for a period of 5 years, brought to present value with a Minimum Rate of Attractiveness (TMA) of 15% per year. An average growth of 4.60% per year was projected on sales revenue. The data provided by the companies surveyed resulted in an IRR of 17.27% per year, compared to a TMA of 15% per year, showing a gain over the TMA of only 2.27%. The project's Payback, that is, the capital invested begins to be recovered after 4 years and 8 months and 20 days, and a projected profitability of 6.34% in the last year of the projection alone. The data presented demonstrate the operational and financial result of this field of activity based on the data collected by the participants, on the decision on economic viability, it is exclusively up to the investor to make this decision.